Exercise protocol and electrical muscle stimulation in the prevention, treatment and readaption of jumper's knee - Basas, A.; Lorenzo, A.M; Gomez, M.-A.; Moreno, C.; Ramirez, C. (New Studies in Athletics, 2014)
ABSTRACT Jumper's knee (patellar tendinitis) is a condition characterised by the appearance of pain in the anterior part of the knee. It is associated with sports activities involving jumping that place a great demand for speed and force on the extensor muscles of the knee. To date many different treatments have been described but no effective protocol has yet been found. In this study six high-level athletes completed a six-month knee readaptation programme over two years consisting of eccentric, isometric, concentric exercises and electrical stimulation with the patellar tendon stretched to maximum tension. Pain was assessed prior to the protocol and at intervals six month using a visual analogue scale (VAS). A clear improvement was observed comparing the initial mean versus those at 18 and 24 months. Diminished pain during the 24 months suggests a direct benefit of this protocol. However, though this study produced hopeful results, the sample size was small and more research is needed.